Knowledge, compliance, and challenges in anti-malarial products usage: a systematic review of at-risk communities for zoonotic malaria - Nurul Athirah Naserrudin; Bipin Adhikari; Richard Culleton; Rozita Hod; Mohammad Saffree Jeffree; Kamruddin Ahmed; Mohd Rohaizat Hassan (BMC, 2024)
Abstract Background Zoonotic malaria is a growing public health threat in the WHO Southeast Asia (SEA) and Western Pacific (WP) regions. Despite vector-control measures, the distribution of Macaque fascicularis and M. nemestrina, and Anopheles mosquitoes carrying non-human simian malaria parasites poses challenges to malaria elimination. The systematic review assesses the literature on knowledge and malaria-preventive practices in zoonotic malaria-affected areas across the WHO SEA and WP, aiming to identify challenges for malaria control. Methods Peer-reviewed articles published in English, Malay and Indonesian between January 2010 and December 2022 were searched in OVID Medline, Scopus, Web of Science, and Google Scholar. Studies of any design-excluding reviews, conference proceedings, and reports from all WHO SEA and WP countries vulnerable to zoonotic malaria-were included. Backwards-reference screening and thematic analysis were conducted. Results Among 4,174 initially searched articles, 22 peer-reviewed articles met the inclusion criteria. An additional seven articles were identified through backwards-reference screening, resulting in a total of 29 articles for this review. Half of these studies were conducted in Cambodia, Myanmar, Malaysia, and Thailand, mainly in forests and remote communities. The review highlighted inconsistencies in the operationalization of knowledge, and five major themes were identified related to knowledge: causation and transmission, symptoms, treatment, severity and complications, and malaria prevention. While participants generally had some understanding of malaria causation/transmission, minority and indigenous ethnic groups demonstrated limited knowledge and held misconceptions, such as attributing malaria to drinking dirty water. Preventive practices included traditional and non-traditional or modern methods-with a preference for traditional approaches to avoid mosquito bites. Challenges to malaria control included feasibility, cost, and access to healthcare services. Conclusion This review provides insights into knowledge, local understandings, and preventive practices related to malaria in the WHO SEA and WP regions. The findings highlight the need for future research to explore the knowledge of at-risk communities regarding zoonotic malaria, their perceive threat of the disease and factors exposing them to zoonotic malaria. New strategies must be developed for zoonotic malaria programs tailored to local contexts, emphasizing the significance of community participation, health education, and socio-behavioural change initiatives. It is important to consider the interconnectedness of human health, environmental and non-human primates conservation. Socio-cultural nuances should also be carefully considered in the design and implementation of these programs to ensure their effect tailored to local contexts.